High fire frequency and the impact of the 2019–2020 megafires on Australian plant diversity. Issue 7 (19th March 2021) - Gallagher, Rachael V.; Allen, Stuart; Mackenzie, Berin D. E.; Yates, Colin J.; Gosper, Carl R.; Keith, David A.; Merow, Cory; White, Matthew D.; Wenk, Elizabeth; Maitner, Brian S.; He, Kang; Adams, Vanessa M.; et al.
Abstract: Aim: To quantify the impact of the 2019–2020 megafires on Australian plant diversity by assessing burnt area across 26, 062 species ranges and the effects of fire history on recovery potential. Further, to exemplify a strategic approach to prioritizing plant species affected by fire for recovery actions and conservation planning at a national scale. Location: Australia. Methods: We combine data on geographic range, fire extent, response traits and fire history to assess the proportion of species ranges burnt in both the 2019–2020 fires and the past. Results: Across Australia, suitable habitat for 69% of all plant species was burnt (17, 197 species) by the 2019–2020 fires and herbarium specimens confirm the presence of 9, 092 of these species across the fire extent since 1950. Burnt ranges include those of 587 plants listed as threatened under national legislation (44% of Australia's threatened plants). A total of 3, 998 of the 17, 197 fire‐affected species are known to resprout after fire, but at least 2, 928 must complete their entire life cycle—from germinant to reproducing adult—prior to subsequent fires, as they are killed by fire. Data on previous fires show that, for 257 species, the historical intervals between fire events across their range are likely too short to allow regeneration. For a further 411 species, future fires during recovery will increase extinction risk as current populations are dominated by immature individuals. Main conclusion: Many Australian plant species have strategies to persist under certain fire regimes, and will recover given time, suitable conditions and low exposure to threats. However, short fire intervals both before and after the 2019–2020 fire season pose a serious risk to the recovery of at least 595 species. Persistent knowledge gaps about species fire response and post‐fire population persistence threaten the effective long‐term management of Australian vegetation in an increasingly pyric world.